Assessment of Genetic Diversity in Two Endemic Aloe Germplasm Populations from Ethiopia Using Morphological Markers - Kahsay, Tewodros; Degu, Hewan Demissie (International Journal of Bio-resource and Stress Management, 2023)
Thirteen Aloe germplasm population; A. adigratana and A. percrassa available at the Ganta Afeshum District (GAD) found in Easter Zone of Tigray were subjected analysis in relation to morphological parameters for estimating the extent of diversity within and between species. The naturally occurring populations at Ganta afeshum District used as data source. Thirteen plots, each measuring 5×20 m2 (100 m2) population-1, were laid down in the study sites. Three individuals per population from each species were randomly sampled to cover variation in growth habit, leaf length, leaf weight, stem length, stem diameter, growth and plant type, leaf color, leaf spot, teeth color, flower color and gel yield. All the genetic individuals and vegetative daughters were sorted, marked and recorded for selected population attributes. Data on the species populations were gathered by using focused group discussions, semi-structured interviews and field observation. The community identified two landraces for Aloe percrassa and four landraces for Aloe adigratana as indicated by their folk taxonomy. Morphological evaluation (of the 13 accessions for selected characters showed qualitative variation among the studied landraces. Maximum similarity of 100% was observed between Population 2 and Population 11 (A. adigratana), Population 12 and Population 5, 7, 8 and 9. While minimum similarity of 11% was observed between Population 3 and Population 6 A. percrassa and A. adigratana. Thus, Aloe landraces maintained at Ganta afeshum District showed high genetic diversity between and within the species. The present study would be useful in genetic improvement and authentication of species and genotype of this medicinally and economically important genus.